Prospects for improving the food and economic security of smallholder maize-based farming systems: a farmer typology approach in Zimbabwe - Manyanga, Mark; Gérard, Françoise; Pedzisa, Tarisayi; Jourdain, Damien; Belard, Amandine; Hanyani-Mlambo, Benjamine; Coquereau, Adrien; Affholder, François (Frontiers in Sustainable Food Systems, 2025)
IntroductionApproximately 70% of communal farmers in Zimbabwe live in poverty, struggling to meet basic needs and provide for their families. These farmers face significant challenges in accessing essential services and resources. This situation makes them a critical subject for study, particularly in the context of smallholder farming systems in sub-Saharan Africa. This study aims to enhance the existing body of knowledge by incorporating a participatory approach and statistical analysis to characterize smallholder farmers and examine their economic and food security status.MethodsWe employed principal component analysis (PCA) and hierarchical cluster analysis (HCA) to classify farmers based on various factors such as cultivated land, livestock ownership, family labor availability, off-farm activities, and remittance receipt. Data was collected from 248 randomly selected households across three purposively chosen wards in the Murehwa district, Zimbabwe.ResultsThe analysis identified four distinct farm clusters: Cluster 1: Highly resource-constrained households, Cluster 2: Moderately resource-endowed households without off-farm income, Cluster 3: Moderately resource-endowed households with access to off-farm income, Cluster 4: Highly resource-endowed households All clusters primarily cultivated maize, their main food source, but showed significant variations in their economic and food security status. The clusters also differed in their levels of resource access, with notable distinctions in the availability of family labor and off-farm income.DiscussionThese findings highlight the need for targeted interventions that provide essential inputs, such as affordable seeds and legumes, to promote crop diversification. Additionally, the study advocates for promoting alternative income sources, such as small livestock and beekeeping, which can enhance food and economic security by reducing the reliance on crop production alone, particularly in the face of uncertain agricultural conditions. These strategies are crucial for improving the livelihoods and resilience of smallholder farmers in Zimbabwe and similar contexts in sub-Saharan Africa.